Immaginari sociali e serie TV: narrazioni e visioni del sentimento nostalgico - Fabio La Rocca (Funes)
TV series are the corollary of observation of the social world through which we encounter the various imaginaries at work in the arcana of reality. The intention here is to illustrate the narrative power of the series as an element that puts into circulation themes of everyday life and our interpretation is realised from the perspective of understanding a worldview shaped by the images, symbols, myths that forms the social imaginary. By means of various examples, we will follow this imaginary excursion in order to detect significant fragments of an imagining of the world. The aim is to show how series indicate narrative elements that constitute the diversity of our society and the implication of the collective imaginary.